Therapeutic Potential of Emerging NAD+-Increasing Strategies for Cardiovascular Diseases - Noemi Rotllan; Mercedes Camacho; Mireia Tondo; Elena M. G. Diarte-Añazco; Marina Canyelles; Karen Alejandra Méndez-Lara; Sonia Benitez; Núria Alonso; Didac Mauricio; Joan Carles Escolà-Gil; Francisco Blanco-Vaca; Josep Julve (MDPI AG, 2021)
Cardiovascular diseases are the leading cause of death worldwide. Aging and/or metabolic stress directly impact the cardiovascular system. Over the last few years, the contributions of altered nicotinamide adenine dinucleotide (NAD+) metabolism to aging and other pathological conditions closely related to cardiovascular diseases have been intensively investigated. NAD+ bioavailability decreases with age and cardiometabolic conditions in several mammalian tissues. Compelling data suggest that declining tissue NAD+ is commonly related to mitochondrial dysfunction and might be considered as a therapeutic target. Thus, NAD+ replenishment by either genetic or natural dietary NAD+-increasing strategies has been recently demonstrated to be effective for improving the pathophysiology of cardiac and vascular health in different experimental models, as well as human health, to a lesser extent. Here, we review and discuss recent experimental evidence illustrating that increasing NAD+ bioavailability, particularly by the use of natural NAD+ precursors, may offer hope for new therapeutic strategies to prevent and treat cardiovascular diseases.